Aplikasi Arsitektur Ekologi Pada Strategi Perancangan Obyek Wisata Edukasi Batik Di Yogyakarta - Abidah Husna; Agus Heru Purnomo; Suparno Suparno (Region : Jurnal Pembangunan Wilayah dan Perencanaan Partisipatif, 2017)
In recent years, public interest in batik industry is on the rise, yet at the same time, records and literatures of the said subject proved to be scarce. These facts, including the designation of Yogyakarta City as “World’s Batik City”, are the background of Batik Educational Tourist Centre in Yogyakarta design proposal. This proposal involves the issue on how the centre caters the activities of the education on batik that also serves the function of tourist attraction. The centre also aims to provide space for information, promotion, production, and sales of batik. Ecological architecture is deemed a suitable method to be used in the proposal based on the reason batik industry produces dangerous wastes; hence the design hopes to educate the batik makers and tourists about environmentally-friendly industry. Batik Educational Tourist Centre in Yogyakarta applies ecological architecture theory, focusing on climactic-adaptive, power-efficient, and environment-conscious aspects.